Chile : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Chile assesses the long-term outlook of Chile's private pension system. The paper provides an overview of Chile's recent experience with public-private partnerships (PPPs), focusing on the design of its institutional framework. The paper discusses that Chile's experience with PPPs, currently covering 44 projects, has been successful. It also analyzes bank profitability and competition in Chile from an international perspective. It also compares Chile's external private debt across industrial and emerging market economies and analyzes implications for external vulnerability.